Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1475-1313.2003.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical procedure to predict the value of temporary occlusion therapy in keratoconjunctivitis sicca

Abstract: Collagen plugs improved tear status in the aqueous deficient dry eyes. Occluding both upper and lower puncta with temporary collagen plugs offers no practical beneficial gain compared with occluding just the lower punctum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…17 We found that the tear menisci returned to near normal levels by 1 day after occlusion. Similar results were reported by Farrell et al 38 and Uchida et al 39 These data indicate insufficient baseline tear volumes in the symptomatic subjects whether or not they wore lenses. Punctal occlusion reduces tear drainage and thereby increases the tear meniscus volume.…”
Section: Discussionsupporting
confidence: 89%
“…17 We found that the tear menisci returned to near normal levels by 1 day after occlusion. Similar results were reported by Farrell et al 38 and Uchida et al 39 These data indicate insufficient baseline tear volumes in the symptomatic subjects whether or not they wore lenses. Punctal occlusion reduces tear drainage and thereby increases the tear meniscus volume.…”
Section: Discussionsupporting
confidence: 89%
“…The one study 19 that reported on the outcomes of artificial tear use indicated nonstatistically significant improvement. Three studies 17,19,21 reported improvement in tear break-up time with the plugs in place. On the basis of the limited findings of this assessment, the dissolving plugs seem to be effective in short-term reduction of symptoms and signs of dry eyes.…”
Section: Efficacymentioning
confidence: 99%
“…The unit of randomization for the included studies was the participant for 11 studies (Altan-Yaycioglu 2005;Chen 2010;Farrell 2003; Kaido 2012;Nava-Castaneda 2003; Qiu 2012; Qiu 2013; Rabensteiner 2013; Roberts 2007;Tsifetaki 2003; Yung 2012), the eye for 5 studies (Brissette 2015; Burgess 2008; Lowther 1995; Mansour 2007;Slusser 1998), and was unclear for 2 studies (Feng 2011; Zhou 2016;).…”
Section: Resultsmentioning
confidence: 99%
“…The unit of analysis was the eye for 7 studies (Brissette 2015;Feng 2011; Kaido 2012; Lowther 1995; Mansour 2007;Qiu 2013; Slusser 1998) although the study investigators did not discuss whether the analyses accounted for the correlation between eyes of a participant. The unit of analysis was unclear for the remaining 8 studies (Altan-Yaycioglu 2005; Burgess 2008; Chen 2010; Farrell 2003;Nava-Castaneda 2003; Qiu 2012; Yung 2012; Zhou 2016). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation